THE ROLE AND PLACE OF CODING THEORY IN IMPROVING THE EFFICIENCY OF INFORMATION TRANSMISSION - Turdina, А.Б.; Semenov, А.Л.; Mubarakov, А.М.; Kerimbayev, А.О. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The main methods of information theory include encoding and decoding. Message encoding solves three tasks: classifying messages; compacting information (compressing information); detecting and correcting random errors in messages. The paper considers in detail one of the tasks of the coding theory - the procedure for compacting information. The earliest code symbols used in compacting information - Morse code-are considered; the features of the Bodo and Fano codes are revealed. In addition, the possibilities of encoding words and sentences in the Kazakh language were studied. The texts in the Kazakh language were studied, the frequency of occurrence of letters, punctuation marks and numbers in the text was found. The amount of "redundant" information in the messages transmitted in the Kazakh language has been calculated and clearly defined.